KAJIAN KONSENTRASI ZAT PENGATUR TUMBUH DAN CEKAMAN AIR TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L): KAJIAN KONSENTRASI ZAT PENGATUR TUMBUH DAN CEKAMAN AIR TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L) - Linuwih Adhi Anggoro; Priyono Priyono; Kharis Triyono (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study aimed to examine the concentration of growth regulators and water stress on the growth and yield of groundnut (Arachis hypogaea l). The study site was conducted at the Research and Collections Garden Faculty of Agriculture Slamet Riyadi University Surakarta  located on Jl. Jaya Wijaya No. 38 Joglo Village Banjarsari District Surakarta City Central Java 57136 with an elevation of ± 105 meters aove sea level. The study was conducted from  May 27 2021 to  August 25 2021. The design used was a completely randomized factorial design (CRD). The types of treatment are: Controlno treatment (D0); ZPT Dekamon 22.43 L with a content of 3.75 ml1 7.5 ml1 11.25 ml1 (D1 D2 D3); Water stress with concentrations of 600mlpolyag 1200mlpolyag 1800mlpolyag (C1 C2 C3). The treatment consisting of 12 treatments and 1 control  was repeated 3 times to otain 36 experimental units. The oserved parameters include visual oservation of the plant plant height (cm) numer of leaves (fiers) wet stem weight (gram) dry stem weight (gram) numer of fruits per tree (fruit) fruit weight per plant (gram) numer of seeds per plant (seeds) dry seed weight per plant (gram) mass of 100 seeds per plant (gram). Data were analyzed using analysis of variance (ANOVA) if significant differences were found data were then  tested using Duncans multiple range test at 5%  to discriminate values. mean etween treatments. The results showed that  D2C2 treatment had the est effect on the visual morphology of plants. At the tree height parameter D3 with the highest average level of 39.63 showed a significant difference in efficiency. This is ecause  growth regulator Dekamon  is an artificial growth regulator that stimulates the growth of stems leaves and plant parts. In the wet stove weight parameter each stress treatment (C) showed a very significant effect the highest average was 15.7 in treatment C3. This is ecause water is needed to achieve maximum quality and quantity of results. The results of the response coefficient analysis (DC) showed that there was no significant difference in the parameters of leaf numer plant height wet stem weight dry stem weight numer of fruits fruit weight numer of fruits and numer of fruits. seeds mass of dry  seeds mass of 100 seeds. among all other treatments. This is due to the genetic nature of plants and external (environmental) factors such as soil water humidity temperature and light.